MODEL KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SDN MARGAPADANG 1 TEGAL - Yusuf Nurrahman; Nourma Ayu Sulistiyowati; Definka Puan Shalika Abdillah; Wiwit Attalikhtia; Bambang Sumardjoko; Sri Lahir (STKIP Pesisir Selatan, 2026)
This study aims to analyze the principal's instructional leadership model in improving the quality of learning at SDN Margapadang 1 Tegal. This study focuses on how the principal implements academic supervision, teacher development, and training to strengthen classroom learning practices. This study uses a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, teacher questionnaires, classroom observations, and document analysis in the form of school work plans, academic supervision schedules, supervision notes, and student learning reports. Data were analyzed thematically using source triangulation to ensure the consistency and credibility of the findings. The findings indicate that the principal implements instructional leadership through scheduled academic supervision, constructive feedback, regular teacher development meetings, and reflective coaching. These practices increase teacher motivation, strengthen teacher confidence, encourage the use of more diverse teaching methods, and create a more open academic culture. However, the impact is not fully distributed across all teachers due to time constraints and the principal's administrative workload. This study proposes an integrated instructional leadership model that combines academic supervision, teacher development, and training in the local context of public elementary schools in Indonesia